2022
DOI: 10.3389/fcimb.2022.988236
|View full text |Cite
|
Sign up to set email alerts
|

In silico characterization of IncX3 plasmids carrying blaOXA-181 in Enterobacterales

Abstract: Carbapenem-resistant Enterobacterales poses a global urgent antibiotic resistance threat because of its ability to transfer carbapenemase genes to other bacteria via horizontal gene transfer mediated by mobile genetic elements such as plasmids. Oxacillinase-181 (OXA-181) is one of the most common OXA-48-like carbapenemases, and OXA-181-producing Enterobacterales has been reported in many countries worldwide. However, systematic research concerning the overall picture of plasmids harboring blaOXA-181 in Enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…We examined SNV prevalence in two primary plasmid clusters whose plasmids were near identical (AA836, AB484). For IncX3/rep_cluster_1195 plasmids carrying bla OXA-181 (AA836), we found remarkably high conservation among plasmid sequences wherein many were 100 % identical to the reference sequence, agreeing with previous studies [ 8 15 69 73 74 ]. Although we found 1–3 SNVs in some plasmid sequences, these were scattered across the genome and did not appear to be linked to any epidemiological information which limits the usefulness of creating a Tn 2013 transposon typing scheme, as done for bla KPC genes with Tn 4401 [ 71 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…We examined SNV prevalence in two primary plasmid clusters whose plasmids were near identical (AA836, AB484). For IncX3/rep_cluster_1195 plasmids carrying bla OXA-181 (AA836), we found remarkably high conservation among plasmid sequences wherein many were 100 % identical to the reference sequence, agreeing with previous studies [ 8 15 69 73 74 ]. Although we found 1–3 SNVs in some plasmid sequences, these were scattered across the genome and did not appear to be linked to any epidemiological information which limits the usefulness of creating a Tn 2013 transposon typing scheme, as done for bla KPC genes with Tn 4401 [ 71 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…Eight isoforms (a to h) of Tn4401 have been identified so far, differing for deletions immediately upstream of the bla KPC gene, with Tn 4401 a and Tn 4401 b being the most common [ 61 ]. In our study, Tn 4401 a was identified in all strains carrying both the bla KPC-3 and bla KPC-31 genes, whereas ColKP3 and IncX3 are reported to be the main promoters involved in the spread of the bla OXA-181 and qnrS1 genes, conferring resistance to carbapenems and fluoroquinolones, respectively [ 62 ]. The presence of different AMR determinants within the same mobile elements highlights the genetic diversity of plasmids and their key role in the diffusion of AMR.…”
Section: Discussionmentioning
confidence: 99%